Alterations in KLRB1 gene expression and a Scandinavian multiple sclerosis association study of the KLRB1 SNP rs4763655 - Søndergaard, Helle Bach (Nature Publishing Group, 2011)
Multiple sclerosis (MS) is a complex autoimmune disease affecting genetically susceptible individuals. A genome-wide association study performed by the International MS Genetics Consortium identified several putative susceptibility genes; among these, the KLRB1 gene is represented by the single-nucleotide polymorphism rs4763655. We could confirm a marginally significant association between rs4763655 and MS (P=0.046, odds ratio=1.06 (1.00–1.13)) in a large Scandinavian case–control study of 5367 MS patients and 4485 controls. The expression of KLRB1 in blood from MS patients was higher compared with healthy controls (P<0.001), and the KLRB1 expression decreased significantly (P<0.001) after interferon (IFN)-β treatment. KLRB1 was expressed in T and natural killer (NK) cells, and expression mainly decreased in NK cells in patients treated with IFN-β. Collectively, our results indicate that KLRB1 gene expression is altered in MS and likely to be involved in the pathogenesis of the disease, whereas rs4763655 in KLRB1 seems to have a minimal role in MS susceptibility.